Fermentation-enabled wellness foods: A fresh perspective - Huan Xiang; Dongxiao Sun-Waterhouse; Geoffrey I.N. Waterhouse; Chun Cui; Zheng Ruan (Food Science and Human Wellness)
Fermented foods represent an important segment of current food markets, especially traditional or ethnic food markets. The demand for efficient utilization of agrowastes, together with advancements in fermentation technologies (microbial- and enzyme-based processing), are stimulating rapid growth and innovation in the fermented food sector. In addition, the health-promoting benefits of fermented foods are attracting increasingly attention. The microorganisms contained in many common fermented foods can serve as “microfactories” to generate nutrients and bioactives with specific nutritional and health functionalities. Herein, recent research relating to the manufacture of fermented foods are critically reviewed, placing emphasis on the potential health benefits of fermentation-enabled wellness foods. The importance of the correct selection of microorganisms and raw materials and the need for precise control of fermentation processes are explored. Major knowledge gaps and obstacles to fermented food production and market penetration are discussed. The importance of integrating multidisciplinary knowledge, communicating with consumers, establishing regulatory frameworks specifically for fermentation-enabled wellness foods and functional fermented foods, are highlighted. Keywords: Fermented foods, Microbial factories, Bioactive, Probiotics, Nutrients, Processing technologies